Penyesuaian Diri Mahasiswa Jawa Yang Merantau Di Padang: Studi Fenomenologi - Firly Dwyka Ra’uf; Adinda Thalia Salsabila; Wilda Yuliana; Febi Septi Wahyuni; Salman Ruhul Jadid; Raissa Aliyyah Putri (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
As migrant students, the process of adjustment becomes a crucial element that determines comfort and success in both academic and social life. Javanese students who move to Padang face significant cultural differences, particularly in communication styles, social values, and community structures. These differences often present challenges in the adjustment process, though they do not necessarily lead to failure or discomfort. This study aims to explore how Javanese students perceive and experience the process of self-adjustment within the Minangkabau cultural environment. The research uses a qualitative approach with a phenomenological method, involving three participants who have studied in Padang for at least four semesters. The results indicate that based on five themes related to adaptation, Javanese students who have moved to Padang do face certain challenges in adapting to their new environment. These include climate and weather conditions, food preferences, language and communication styles, as well as social interactions and norms. In response to these challenges, the migrant students employ various adaptation strategies, such as self-management, avoiding sources of conflict, keeping busy, and self-motivation. However, not all students adopt the same strategies. They each have their own adaptation strategies, influenced by their life experiences and personalities. The supporting factors in adaptation for migrant students include social support, whether from family, friends, or the community.